Inhalationally administered semifluorinated alkanes (SFAs) as drug carriers in an experimental model of acute respiratory distress syndrome - Otto, Matthias; Krebs, Jörg; Welker, Peter; Holm, René; Thiel, Manfred; Gattinoni, Luciano; Quintel, Michael; Tsagogiorgas, Charalambos (Pharmaceutics, 2021)
Aerosol therapy in patients suffering from acute respiratory distress syndrome (ARDS) has so far failed in improving patients’ outcomes. This might be because dependent lung areas cannot be reached by conventional aerosols. Due to their physicochemical properties, semifluorinated alkanes (SFAs) could address this problem. After induction of ARDS, 26 pigs were randomized into three groups: (1) control (Sham), (2) perfluorohexyloctane (F6H8), and (3) F6H8-ibuprofen. Using a nebulization catheter, (2) received 1 mL/kg F6H8 while (3) received 1 mL/kg F6H8 with 6 mg/mL ibuprofen. Ibuprofen plasma and lung tissue concentration, bronchoalveolar lavage (BAL) fluid concentration of TNF-α, IL-8, and IL-6, and lung mechanics were measured. The ibuprofen concentration was equally distributed to the dependent parts of the right lungs. Pharmacokinetic data demonstrated systemic absorption of ibuprofen proofing a transport across the alveolo-capillary membrane. A significantly lower TNF-α concentration was observed in (2) and (3) when compared to the control group (1). There were no significant differences in IL-8 and IL-6 concentrations and lung mechanics. F6H8 aerosol seemed to be a suitable carrier for pulmonary drug delivery to dependent ARDS lung regions without having negative effects on lung mechanics.
Gesehen am 29.07.2021